Laproscopic Management of Wandering Biliary Ascariasis - Umesh Jethwani; G. J. Singh; P. Sarangi; Vipul Kandwal (Case Reports in Surgery)
Ascariasis is one of the most common helminthic diseases in humans, occurring mostly in countries with low standards of public health and hygiene, thereby making ascariasis highly endemic in developing countries. In endemic areas, 30% of adults and 60–70% of children harbour the adult worm. Biliary ascariasis is a rare cause of obstructive jaundice. Conventional management involves endoscopic extraction of worm. We are reporting a rare case of ascaris which induced extrahepatic biliary obstruction in a young male who presented with acute cholangitis. The ascaris was removed by laparoscopic exploration of the common bile duct. Postoperative period was uneventful.